A Successful Whole Body Therapeutic Hypothermia for Hypoxic Ischemic Encephalopathy During an ECMO Run in a Newborn - Okulu, Emel; Erdeve, Omer; Pekcici, Bahar Bingoler; Kendirli, Tanil; Eyileten, Zeynep; Atasay, Begum; Arsan, Saadet (Frontiers in Pediatrics, 2019)
There is a limited data regarding the safety of using therapeutic hypothermia (TH) together with extracorporeal membrane oxygenation (ECMO) in neonates with both hypoxic ischemic encephalopathy (HIE) and respiratory failure. We report a newborn who had meconium aspiration syndrome and HIE, received both TH and ECMO without any complication.